2020
DOI: 10.14569/ijacsa.2020.0110638
|View full text |Cite
|
Sign up to set email alerts
|

ER Model Partitioning: Towards Trustworthy Automated Systems Development

Abstract: In database development, a conceptual model is created, in the form of an Entityrelationship(ER) model, and transformed to a relational database schema (RDS) to create the database. However, some important information represented on the ER model may not be transformed and represented on the RDS. This situation causes a loss of information during the transformation process. With a view to preserving information, in our previous study, we standardized the transformation process as a one-to-one and onto mapping f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…The n_estimators parameter for Random Forest models was the number of Decision Trees used. 37,38 Previous studies have observed that a higher max_depth resulted in overfitting and convoluted decision-making. 31 The model did not generalize as well and prioritized making decisions on insignificant features.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The n_estimators parameter for Random Forest models was the number of Decision Trees used. 37,38 Previous studies have observed that a higher max_depth resulted in overfitting and convoluted decision-making. 31 The model did not generalize as well and prioritized making decisions on insignificant features.…”
Section: Methodsmentioning
confidence: 99%
“…A larger n_estimator value led to overfitting and insignificant feature decisions. 38 To prevent the model from overfitting, the optimal value was found to be at 36 after testing for the n_estimator in the range 1 to 45 (Figure 4b).…”
Section: Methodsmentioning
confidence: 99%
“…Эти редакторы имеют специфическую функциональность, такую как генерация диаграмм из программного кода в сочетании с генерацией программного кода из диаграмм (roundtrip engineering). В доступных научных публикациях исследуется повышение надежности автоматизированных систем в ходе трансформации диаграмм за счет сегментирования модели [1]. Обсуждаются программные средства для автоматического создания визуальных композиций на основе диаграмм [2].…”
unclassified